2018
DOI: 10.18087/cardio.2018.3.10093
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Gene Polymorphisms of Matrix Metalloproteinases (-9, -12 and -20) and Collagen Type I Degradation Products With the Remodeling of the Left Ventricle in Patients With Acute Myocardial Infarction

Abstract: Ассоциация генных полиморфизмов матриксных металлопротеиназ (-9,-12 и-20) и продуктов деградации коллагена I типа с постинфарктным ремоделированием левого желудочка

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Only a few studies were found about the association of the MMP-9 genotype with the size of the heart chambers. In patients with acute myocardial infarction, the presence of the G allele of the rs17576 polymorphism MMP-9 gene and other factors increased the likelihood of hypertrophic left ventricular remodeling [27]. Also, the presence of the minor allele G of the rs17576 polymorphism of the MMP-9 gene and the C allele of the MMP-20 rs2245803 gene (CK = -2.228) enhanced its association with hypertrophic changes in left ventricle geometry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies were found about the association of the MMP-9 genotype with the size of the heart chambers. In patients with acute myocardial infarction, the presence of the G allele of the rs17576 polymorphism MMP-9 gene and other factors increased the likelihood of hypertrophic left ventricular remodeling [27]. Also, the presence of the minor allele G of the rs17576 polymorphism of the MMP-9 gene and the C allele of the MMP-20 rs2245803 gene (CK = -2.228) enhanced its association with hypertrophic changes in left ventricle geometry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Диастолическая дисфункция ЛЖ (ДДЛЖ) является одним из патогенетических механизмов 2 , p χ 2 = 6,11 p = 0,00124 χ 2 = 9,9 p = 0,00001 χ 2 = 5,9 p =0,0123 χ 2 = 6,98 p=0,00001 аллель -786T данного гена, встречается достоверно чаще у лиц с нормальными значениями СПВ.…”
Section: результатыunclassified
“…Содержащиеся в доступной литературе сведения свидетельствуют о несомненной клинической значимости изучения полиморфизма генов у больных с сердечно-сосудистыми заболеваниями (ССЗ) с точки зрения возможности стратификации риска развития ССО на основании генетического тестирования [2][3][4].…”
Section: Introductionunclassified